2023 Joint Leave Holiday Creativity Through Minangkabau Int'l Airport According To Islamic Education - Herry Zulman; Martin Kustati; Nana Sepriyanti; Nurhasnah Nurhasnah (International Journal of Economics, Business and Innovation Research, 2024)
At the end of the year, the dream of every individual is a vacation and time off, often involving the use of air travel for comfort, smoothness, and speed. The impact of COVID-19 has led to fatigue due to routines for over a year, affecting people of all ages, including parents, children, and grandparents. Therefore, it is crucial to enjoy a vacation as a form of rejuvenation. Common challenges every year include expensive tickets, human movement congestion, traffic jams, delays, and increased prices of products at tourist destinations. In evaluating holidays and joint leave with six people (parents-in-law and two elementary school children) from the perspective of Islamic teachings, the author aims to make the vacation enjoyable, entertaining, and fitness-enhancing for the participants, following the guidance in the Quran, as found in Surah Al-Jumuah/62: 10. Despite the high cost and difficulty in obtaining airline tickets, Minister of Transportation Decree No. 106 of 2019 regarding the Upper Limit Tariff (TBA) and Lower Limit Tariff (TBB) for Domestic Air Transport allows airlines to use upper limit ticket prices during the holiday season (peak season). Before the holiday season arrives, they use lower limit tariffs that are more affordable. The author identifies eight strategies that prospective air passengers need to prepare, including planning, choosing tourist destinations, financial preparation, early ticket reservations, cost savings, physical and mental preparation, creative thinking, and increased patience from the outset. Through thorough planning, it is expected that holidays and joint leave will bring satisfaction to all parties.